Health-related quality of life following bisphosphonate therapy in individuals with Paget’s disease of bone – A study from a teaching hospital in Southern India - Fibi K. Ninan; Kripa Elizabeth Cherian; Remya Rajan; Felix Jebasingh; Nitin Kapoor; Hesarghatta S. Asha; Nihal Thomas; Thomas V. Paul (Journal of Family Medicine and Primary Care)
Background: Paget’s disease of bone (PDB) is associated with considerable morbidity because of bony pains, fractures, and deformities. Remission, as assessed by reduction in alkaline phosphatase levels, does not necessarily correlate with improvement in quality of life (QoL). Health-related quality of life (HR-QoL) in affected individuals is not well-studied in India. This study attempts to describe the QoL in individuals with PDB. Methods: In this prospective observational study spanning 6 years (Jan 2017–Dec 2022), we included 29 treatment-naïve patients diagnosed with PDB based on clinical, biochemical, and radiographic features. All patients received treatment with antiresorptive agents. SF-36 questionnaire was administered before treatment and at review. Results: A total of 29 patients with PDB (20 males), with a mean (SD) age of 68.1 (9.8) years, were included. Symptomatic disease was seen in 23/29 (79.3%) and polyostotic disease in 25/29 (86%) subjects. The median duration of symptoms was 6 months (0–24 months). The most frequently involved skeletal sites were the pelvis (69%), vertebrae and sacrum (68%), followed by the skull (48%) and lower limb (48%). The subjects were treated with parenteral zoledronate (65.5%), oral alendronate (24.1%), and denosumab (6.9%). There was a significant improvement in all eight domains of QoL (P = 0.0001) as assessed by the SF-36 questionnaire. The maximum improvement (27.2%) was observed in the physical functioning domain (P = 0.0001). Conclusion: This study assessed various domains in QoL by using the SF-36 questionnaire at baseline and post-treatment with antiresorptive agents, and it was noted that there was a significant improvement in all domains of QoL.